When property is guilty of a crime: civil forfeiture under the Anti-Money Laundering and Anti-Terrorism Financing Act (AMLATFA) 2001 / Zaiton Hamin, Normawati Hashim and Muhammad Muaz Abdul Hakim - Hamin, Zaiton; Hashim, Normawati; Abdul Hakim, Muhammad Muaz (2014)
Anti-Money Laundering and Anti-Terrorism Financing Act 2001 (AMLATFA) was created not only to criminalise money laundering and terrorism financing, but also to allow freezing and seizure of assets that are the proceeds of the above-mentioned crimes. The 2001 Act was also aimed at providing for forfeiture or confiscation proceedings of assets or the evidence of such crimes by the government. Prior to the 2001 Act, confiscation cases almost exclusively centered on drug trafficking under the Dangerous Drug (Forfeiture of Property) Act 1988. The 2001 Act is concerned with two types of forfeiture namely, criminal forfeiture in which the forfeiture is upon prosecution and civil forfeiture when there is no prosecution. This conceptual paper which is drawn from an ongoing research, seeks to examine the latter type of forfeiture in order to understand its origin, the rationale and the manner in which such forfeiture could be subjected to abuse, as experiences in other jurisdictions have indicated. The authors contend that civil forfeiture law as contained in AMLATFA 2001 represents one of the most serious encroachments on private property rights. Not only that, such legal rule has made property and not the owner to be guilty until proven innocent. This paper employs a doctrinal legal analysis and secondary data, which analyse the primary source, which is the AMLATFA 2001 itself, and secondary sources including case law, articles in academic journals, books and online databases.